The Insertion of Syrian Refugees in the Egyptian Labor Market: with Special Focus on Food and Restaurants Sector - Hassan, Mai Ali (AUC Knowledge Fountain, 2021)
This thesis is about the insertion of Syrian refugees in the Egyptian labor market. It specifically focuses on this insertion in the food and restaurants sector. It reviews the theoretical literature that tackled the economic integration of refugees and asylum seekers. It also examines the legal framework governing refugees in Egypt as well as the legal apparatus provisions related to their employment. Both are factors determining the access of refugees to the Egyptian labor market. The thesis finds that other economic and social factors also determine and facilitate the access of Syrian refugees to the Egyptian labor market. In the food and restaurant sector, demand for and supply of the Syrian products. Another economic factor is the sizable informal sector which despite its disadvantages, offers an opportunity to access the labor market. Syrian investments in Egypt injected capital and created jobs for refugees and Egyptians alike. Social connections in forms of bonds among Syrians and bridges with hosting communities are found to have a fundamental role in their insertion. While the bureaucratic process of obtaining or renewing permits as well as the weak links with the government pose some challenges, thanks to the presence of international organizations, whether IGOs or NGOs, that promote Syrian refugees’ resilience through building on their capacities, Syrians are able to meet the labor market needs. The operation of the legal, economic and social factors, in addition to support from international organizations, has favored the employment of Syrian refugees in the Egyptian food and restaurants sector but in the informal sector due to the bureaucratic hurdles of obtaining or renewing permits and of the legal requirements they must fulfill. Despite the numerous challenges they face, Syrian refugees are taking the advantage of their social connections to support themselves and ensure their livelihoods.